Vibrationally resolved electron-impact excitation cross sections for singlet states of molecular hydrogen. (27th June 2018) - Tapley, Jonathan K; Scarlett, Liam H; Savage, Jeremy S; Zammit, Mark C; Fursa, Dmitry V; Bray, Igor
Abstract: We present calculations of vibrationally resolved cross sections for excitation of the B 1 Σ u +, C 1 Π u, B ′ 1 Σ u +, D 1 Π u, and E, F 1 Σ g + electronic states of molecular hydrogen. Here we apply the adiabatic nuclei convergent close-coupling method formulated in two-center prolate spheroidal coordinates. We find significant disagreement with previous calculations, where available.